A Comprehensive Review of Pediatric Glaucoma Following Cataract Surgery and Progress in Treatment. Issue 1 (13th January 2023) - Zhang, Yu; Song, Yunhe; Zhou, Yue; Bai, Bingyu; Zhang, Xiulan; Chen, Weirong
Abstract : Glaucoma following cataract surgery (GFCS) remains a serious postoperative complication of pediatric cataract surgery. Various risk factors, including age at lensectomy, intraocular lens implantation, posterior capsule status, associated ocular/systemic anomaly, additional intraocular surgery, and a family history of congenital cataract and GFCS, have been reported. However, the optimal surgical approach remains unclear. This review evaluates the diagnostic criteria, classification, risk factors, mechanism, and surgical management, especially the efficacy of minimally invasive glaucoma surgery, in GFCS, and aims to propose an optimal clinical management strategy for GFCS. The results of our review indicate that ab interno trabeculotomy (goniotomy) may be the most appropriate first-line treatment for GFCS.